Apoyo y seguimiento en la ejecución de proyectos de infraestructura del municipio de Gámeza (2023)
As part of the undergraduate project and dissemination article, while undertaking an internship as a civil engineering degree requirement, active participation in a work placement in the municipality of Gámeza was carried out, providing support and monitoring for municipal infrastructure projects. The main objective of this initiative was to optimize the development and management of projects, ensuring their quality and compliance. To achieve this purpose, methodologies were implemented that included detailed analysis, constant supervision, and close collaboration with municipal staff and contractors. The results achieved reflect significant progress in project execution; furthermore, active collaboration with interested communities within the municipality allows for greater community participation in the process. Key conclusions highlight the importance of collaborative work among the municipality of Gámeza, contractors, and municipal administration, emphasizing the sustainable development of the most affected communities, as well as the relevance of continuous supervision and adaptability in infrastructure project management. This approach not only benefits the municipality of Gámeza in terms of improved infrastructure but also lays the groundwork for promoting more equitable and sustainable municipal development.